Initial experience of ureteric visualization using methylene blue during laparoscopy for gynecological surgery - Shao, Ruyu; Shen, Faquan; Soleymani majd, Hooman; Qin, Xiaoqing; Yao, Desheng; Long, Ying; Wang, He; Wei, Yousheng; Chang, Xin (Frontiers in Surgery, 2024)
Objectives Iatrogenic ureteral injury is a severe surgical complication, with a highest incidence of 1.5% in gynecological surgeries. The purpose of this report is to document our initial experience with using methylene blue (MB) to label the ureter in gynecological laparoscopic surgeries and to explore its effectiveness and safety. This is also a novel description of simultaneously visualizing ureteral MB fluorescence and sentinel lymph nodes (SLN's) Indocyanine Green (ICG) fluorescence using the same camera. Methods This study included patients undergoing gynecological laparoscopic surgeries, with the same surgeon performing all cases. During the early stages of each surgery, rapid intravenous infusion of MB was administered. For cases requiring SLN imaging, we also injected ICG solution into the cervix. Assessment of the included cases was conducted both intraoperatively and postoperatively. The group that had MB fluorescence (Group A) was compared to a control group that did not have it (Group B). Results A total of 25 patients (Group A) received MB during surgery, demonstrating 45 ureters clearly, with an imaging success rate of 90%. Continuous and clearer fluorescence imaging was achieved in cases with ureteral hydronephrosis. In most patients, ureteral fluorescence was visible 15–20 min after intravenous infusion of MB, and 64% still exhibited fluorescence at the end of the surgery. In patients who had both ICG and MB, dual fluorescence imaging was achieved clearly. Among the included cases, there were no iatrogenic ureteral injuries (0%), which we observed to be lower than in patients who did not receive MB (1.3%). The rate of adverse events was similar in both groups. Conclusion Using MB fluorescence is an effective and safe method of visualizing the ureters during gynecological surgeries, and can diminish iatrogenic ureteral injury without increased associated adverse events. It therefore may offer promising prospects for clinical application.